Evaluating the Influence of MTU Configuration on Network Performance within a Software-Defined Networking Architecture Employing Mininet and the Ryu Controller - Hane Yorda Dinata; Daryan Pratama Alifi; Abdull Kheqal (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2026)
This study examines how variations in Maximum Transmission Unit (MTU) affect network performance in a Software-Defined Networking (SDN) architecture using the Ryu controller, Mininet, and Open vSwitch. Experiments were conducted in a virtualized Ubuntu 18.04 environment with four MTU settings 500, 1000, 1500, and 2000 bytes and performance was evaluated through repeated measurements of Round Trip Time (RTT), throughput, jitter, and packet loss. All scenarios produced 0% packet loss, enabling focused analysis on latency, efficiency, and temporal stability. The results indicate that MTU size has a non-linear influence on SDN behavior. The 1000-byte MTU yielded the lowest RTT (10.9 ms), while larger and smaller values introduced higher delay. Throughput peaked at 1500 bytes (11.4 Mbps) but declined sharply at 2000 bytes, reflecting inefficiencies in processing oversized packets. Jitter showed a distinct pattern, remaining low at 500 bytes, increasing at mid-range MTUs, and decreasing again at 2000 bytes, suggesting sensitivity to internal buffering and queue dynamics. Overall, MTU values between 1000 and 1500 bytes offer the most balanced performance across latency, throughput, and jitter. These findings highlight the need for careful MTU selection to optimize the operational stability and efficiency of SDN-based networks.